Protective effect of baicalin against pulmonary arterial hypertension vascular remodeling through regulation of TNF‐α signaling pathway. Issue 1 (9th January 2021) - Xue, Xia; Zhang, Shanshan; Jiang, Wen; Wang, Jue; Xin, Qian; Sun, Chao; Li, Kailin; Qi, Tonggang; Luan, Yun
Abstract: Pulmonary arterial hypertension (PAH) is a progressive cardiovascular disease with high mortality. However, there were no efficient medical drugs for PAH to enormously improve the survival and quality of life measures. The present study aimed to explore the protective effect of baicalin against experimental PAH in vivo and vitro. All the experimental rats received intraperitoneal injection of monocrotaline (MCT) to induce PAH model. Baicalin was given by intragastric administration from 2 days after MCT injection. Forty animals were randomly divided into four groups: Control, MCT, saline‐, and baicalin‐treated groups ( n  = 10 in each). Post‐operation, hemodynamic data, and index of right ventricular hypertrophy (RVHI) were recorded to evaluate the inhibition of baicalin on MCT‐induced PAH. Furthermore, pulmonary artery smooth muscle cells (PASMCs) model induced by tumor necrosis factor‐α (TNF‐α) was used to observe the inhibition of vascular cells proliferation in vitro. The results demonstrated that baicalin significantly attenuated MCT‐induced right ventricular systolic pressure (RVSP), the index of right ventricular hypertrophy, and vessel wall thickness; inhibit inflammatory and cell proliferation induced by MCT or TNF‐α, respectively. In addition, we found that baicalin might protect against experimental PAH via regulating the TNF‐α/BMPR2 signaling pathway. Abstract : Our present study demonstrated that: Baicalin could attenuate MCT‐induced pulmonary vascular remodeling through inhibition inflammatory response. Baicalin could reduce the protein expression of Nuclear factor‐κB (NF‐κB), intercellular cell adhesion molecule‐1 (ICAM1) and vascular cell adhesion molecule‐1 (VCAM1), but increased the vascular remodeling associated protein factors BMPR2, ID1, and Smad1//5/8 in MCT‐PH rats. Baicalin could inhibit TNF‐a‐PAMSC proliferation in vitro through regulation of BMPR2 signaling pathway.